Risk factors associated with poorly controlled diabetes in a rural population of Karnataka: a case-control study - Blah, Alisha N.; George, Carolin E.; Mukherjee, Devashri; Norman, Gift (International Journal of Research in Medical Sciences, 2017)
Background: The worldwide prevalence of diabetes has risen dramatically over the past two decades. India with the highest absolute number of cases has become the diabetes capital of the world. The aim of the study was to identify the factors associated with poorly controlled diabetes and comparing them between poorly controlled and well controlled subjects. Methods: This is a case-control study carried out in a rural population of villages in Devanahalli Taluk, Karnataka. Study population included adults above 20 years having type II diabetes for a minimum of one year currently under treatment. 50 poorly controlled and 50 well controlled patients willing to participate were enrolled for the study. A pre-determined questionnaire was used after taking a verbal consent from each participant. Results: Long duration of diabetes, presence of co-morbidities, irregular visit to physicians and skipping medicines were the factors associated with poorly controlled diabetes. Conclusion: The study emphasizes that regular follow up and control of co-morbidities are important factors in optimal control of disease.